Studies on double selenates. Part 12. Thermal decomposition of ammonium selenate and of double selenates of lanthanide, and yttrium, and ammonium - Crespi, M.Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 1994)
Thermogravimetry (TG) up to 900°C, differential thermal analysis (DTA) up to 1100°C and gravimetric data up to 1200°C, have been used to study the thermal decomposition of ammonium selenate and of the double selenates of lanthanides, and yttrium, and ammonium. The results provided the composition and thermal stability and also an interpretation of the thermal decomposition mechanisms. © 1994.